Coherent approach to transport and noise in double-barrier resonant diodes - Aleshkin, V. Ya (2004)
We implement a quantum approach which includes long range Coulomb interaction and investigate current voltage characteristics and shot noise in double-barrier resonant diodes. The theory applies to the region of low applied voltages up to the region of the current peak and considers the wide temperature range from zero to room temperature. The shape of the current voltage characteristic is well reproduced and we confirm that even in the presence of Coulomb interaction the shot noise can be suppressed with a Fano factor well below the value of 0.5. This feature can be an indication of coherent tunneling since the standard sequential tunneling predicts in general a Fano factor equal to or greater than the value 0.5. This giant suppression is a consequence of Pauli principle as well as long range Coulomb interaction. The theory generalizes previous findings and is compared with experiments.